1
$\begingroup$

Trying to answer this question and I am fairly new to Dirac Notation:

Let $|\psi\rangle$ and $|\phi\rangle$ be two states in a Hilbert Space and consider the linear operator $A:=|\psi\rangle\langle\phi|$. Show that the adjoint is given by $A^\dagger=|\phi\rangle\langle\psi|$.

Here's my go at it.

Using the definition for the adjoint as $$\langle A^{\dagger}x|y\rangle=\langle x| Ay\rangle$$ Using the right side we achieve $\langle x|\psi\rangle\langle \phi|y\rangle$. Now $$\langle x|\psi\rangle\langle \phi|y\rangle=\langle A^{\dagger}x|y\rangle$$ Inputting the given expression for $A^\dagger$ I get $$\langle x|\psi\rangle\langle \phi|y\rangle=\langle|\phi\rangle\langle\psi|x\rangle|y\rangle$$

I am unsure of what happens at $\langle|\phi\rangle$ and can't see how these two equate. If anyone could point me in the right direction I would greatly appreciate it.

$\endgroup$
  • 1
    $\begingroup$ Notice that the dot product is sesquilinear. We then have $\langle A^{\dagger}x|y\rangle=\langle y| A^{\dagger}x\rangle ^*=\langle y| \phi\rangle ^*\langle\psi|x\rangle^*=\langle x| \psi \rangle\langle \phi | y\rangle$, as required. $\endgroup$ – vnd Nov 9 '15 at 20:17
1
$\begingroup$

The Dirac notation gets sometimes confusing and it may help to write everything using the standard Hilbert space notation (which is almost the same as Dirac's). Now:

Let $H$ be the Hilbert space and $\langle \cdot, \cdot \rangle$ the inner product. Fix $\psi, \varphi \in H$. Define the operator $A: H \to H$ by $$ Ax = \psi \langle \varphi, x \rangle $$ and the operator $A^\dagger: H \to H$ by $$ A^\dagger x = \varphi \langle \psi, x \rangle\,. $$ Now $$ \langle x, Ay \rangle = \langle x, \psi \rangle \langle \varphi, y \rangle $$ and $$ \langle A^\dagger x, y \rangle = \langle \psi, x \rangle^* \langle \varphi, y \rangle = \langle x, \psi \rangle \langle \varphi, y \rangle\,, $$ where I assumed that the inner product is linear in the second variable and conjugate-linear in the first variable. Thus $A^\dagger$ is the Hermitian adjoint of $A$.

Edit: The problem with your computation is that you misinterpreted $\langle A^\dagger x|$. Because $| A^\dagger x \rangle = | \phi \rangle \langle \psi | x \rangle $ we get $$ \langle A^\dagger x| = \langle x | \psi \rangle \langle \phi |\,. $$

$\endgroup$
0
$\begingroup$

I would use that $\langle x|y\rangle=\langle y|x\rangle^*.$ Hence $$\langle A^{\dagger}x|y\rangle=\langle y|A^\dagger x\rangle^*=(\langle y|\phi\rangle\langle \psi|x\rangle)^*=\langle y|\phi\rangle^*\langle \psi|x\rangle^*=\langle \phi|y\rangle\langle x|\psi\rangle=\langle x|Ay\rangle.$$


Edit. Since vnd commented before me I will additionaly write some general feature.

If $B=|\phi\rangle\langle\psi|,$ then $$\langle Bx|y\rangle=\langle y|B x\rangle^*=(\langle y|\phi\rangle\langle \psi|x\rangle)^*=\langle y|\phi\rangle^*\langle \psi|x\rangle^*=\langle \phi|y\rangle\langle x|\psi\rangle.$$ Hence we can expand Dirac notation to $\langle Bx|y\rangle,$ where $B=|\phi\rangle\langle\psi|,$ in such a way that $$\langle Bx|y\rangle=\langle \phi|y\rangle\langle x|\psi\rangle.$$ And since it follows from properties it is the only reasable way to write it.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.